Roasting and extruding affect nutrient utilization from soybeans in 10- and 20-lb pigs - Kim, I.H.; Gugle, Terry L.; Hines, Robert H.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Ninety nursery pigs were used in two metabolism experiments to determine the effects of roasting and extruding on the nutritional value of Williams 82 soybeans with (+K) and without (-K) gene expression for the Kunitz trypsin inhibitor. Treatments for both experiments were: 1) soybean meal; 2) +K roasted; 3) +K extruded; 4) -K roasted; and 5) -K extruded. The roasting and extrusion treatments were accomplished with a Roast-A-Tron8 roaster and an InstaPr0 8 extruder. Diets were the soybean preparations (96.5% of the diet) with only vitamins and minerals added as needed to meet or exceed NRC requirements. Daily feed allowance was 5% of initial body wt given as three equal meals. In Exp. I, 50 weanling pigs (10.4 Ib average body wt and 21 d average age) were used. Apparent values for N digestibility, biological value (BV), percentage N retention, gross energy (GE) digestibility, and metabolizable energy (ME) were greater for pigs fed extruded soybeans compared to pigs fed roasted soybeans. Also, N digestibility, BV, and percentage N retention were greater for pigs fed -K soybeans compared to those fed + K soybeans. In Exp. 2, 40 pigs (21.4 lb average body wt and 35 d average age) were allowed to adjust to the nursery environment before use in the experiment. In general, the pigs in Exp. 2 (Le., the older pigs) had greater utilization of nutrients from all of the soybean products than the younger pigs used in Exp. 1. Digestibilities of OM, N, and GE were greater for pigs fed -K soybeans compared to those fed + K soybeans, and extruded soybeans gave greater digestibilities of OM, N, and GE compared to roasted soybeans. Also, percentage N retention and percentage ME were greater for pigs fed extruded soybeans were greater than for pigs fed roasted soybeans. In conclusion, extruded and -K soybeans were of greater nutritional value than roasted and + K soybeans for 10- and 20-lb nursery pigs.
Keywords: Swine; Pig; Soybean; Roast; Extrude; Metabolism; Nitrogen retention